Partial Discharge Detection from Large Motor Stator Slots Using EFPI Sensors - Jinlong Wang; Weizhong Sun; Jun Zhou; Lei Wang; Lianfei Chen; Pengcheng Chen; Qichao Chen; Weichao Zhang (Sensors)
This study addresses the challenges of electromagnetic interference and unstable signal transmission encountered by traditional sensors in detecting partial discharge (PD) within stator slots of large motors. A novel Extrinsic Fabry–Perot Interferometer (EFPI) sensor with a vibration-coupling air gap was designed to enhance the narrowband resonant detection sensitivity for PD ultrasonic signals by optimizing the diaphragm structure and coupling interface. The sensor features a quartz diaphragm with a thickness of 20 μM, an effective constrained radius of 0.9 mm, a vibration-coupling air gap depth of 100 μM, and a first-order natural resonant frequency of 66 kHz. Simulation and experimental analyses revealed the distribution characteristics and propagation paths of ultrasonic signals within stator slots. The results demonstrate that the EFPI sensor effectively detects PD ultrasonic signals at its resonant frequency of 66 kHz with a localization error of less than 5 mm, meeting engineering requirements. This study provides theoretical and practical insights into the efficient detection and precise localization of insulation faults in large motor stators.